A Bibliometric Analysis on Satisfaction and Loyalty in Homestay - Amin Kiswantoro; Sugiarto; Tonny Hendratono; Dwiyono Rudi Susanto; Damiasih; Nur Rohman; Rizky Maulana (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the mapping of research into several scopes of the tourism sector by discussing several topic parameters regarding satisfaction, loyalty, and homestay which were published during 2017 – 2022 and indexed on Google Scholar, analyzing topics related to Satisfaction and Loyalty in Homestay. This study uses a qualitative method with a thematic analysis approach as a data analysis method. This research utilizes the Publish or Perish (PoP) application to collect research data from research results indexed on Google Scholar by entering the keywords